Exploring polypharmacy phenomenon in newly diagnosed relapsing-remitting multiple sclerosis: a cohort ambispective single-centre study - Aurora Zanghì; Emanuele D'Amico; Salvatore Lo Fermo; Francesco Patti (SAGE Publishing, 2021)
Aims: We aimed to examine the frequency of polypharmacy in a large cohort of patients at the time of diagnosis of relapsing-remitting multiple sclerosis (RRMS) and to explore its effects on discontinuation of first disease-modifying treatment (DMT) using survival analysis. Methods: This was a cohort ambispective single-centre study. We enrolled RRMS patients starting their first DMT between 1st January 2013 and 31st December 2015. According to the number of medicines prescribed (except DMTs), we divided the patients into three groups: no-poly RRMS, minor-poly RRMS (from one to three medications), and major-poly RRMS (more than three medications). Results: A total of 392 RRMS patients were enrolled (mean age 41.1). The minor-poly RRMS group included 61 patients (15.6%) and the major-poly RRMS group included 112 (28.6%). Individuals in these groups were older and had higher median body mass index (BMI) than patients in the no-poly RRMS group ( p  < 0.05). Upon multinomial regression analysis, older age at onset was associated with minor and major polypharmacy (OR 1.050, CI 1.010-1.093, p  = 0.015 and OR 1.063, CI 1.026-1.101, p  = 0.001, respectively) and higher BMI was associated with major polypharmacy (OR 1.186, CI 1.18-1.29, p  = 0.001). The rates of discontinuation of first DMT were similar among the three groups (50.7% for no-Poly RRMS, 50.8% for minor-Poly RRMS, and 53.3% for major-Poly RRMS, p  = 0.264). At log-Rank test, there were no differences among the three groups ( p  = 0.834). Conclusion: Polypharmacy was more common in older RRMS patients with high BMI.